Implementasi Strategi Reading Aloud Untuk Meningkatkan Pemahaman Literasi Pendidikan Dalam Kurikulum Merdeka SDN Mangunharjo 6 - Ryzca Siti Qomariyah; Mustika Kirana Putri; Ajunaida Kurniawati; Putri Shofiya Nur Hasanah (CV. ITTC INDONESIA, 2023)
Implementation of the Reading aloud strategy to increase understanding of educational literacy in the SDN Merdeka Mangunharjo 6 curriculum. This study aims to improve students' literacy understanding through fun reading strategies.The subjects of this study were all 21 grade III students consisting of 12 boys and 9 girls. The research was carried out for 2 meetings, where each meeting was started by giving ice breaking with the aim of increasing students' enthusiasm before receiving learning in any form, after that giving literacy and then continuing with giving a question that was used to measure the level of students' understanding of the reading contained in the pretest and posttest. The results showed that there was an increase in students' understanding of literacy after using the reading aloud strategy.